Understanding the impact of silver as an emerging contaminant in the Ibaizabal and Gironde estuaries - Rementeria Ugalde, Ane (CCSD, 2016)
Estuaries have been subjected to a high human pressure which has led to the presence of pollutants in their waters and sediments including trace metals. The estuaries in the Bay of Biscay do not constitute an exception of this situation and the Ibaizabal and Gironde Estuaries are both very well known for having high metal concentrations in different compartments. In this context, environmental health monitoring programmes have relied on the use of mussels and oysters as sentinel organisms because chemical and biological analyses of their tissues allow assessing the general health status of their surrounding environment. The present work aims at acquiring a deeper understanding of the interactions between bioaccumulation and the toxic effects of copper (Cu) and silver (Ag) in oysters Crassostrea gigas, as well as the effects that environmental factors may have on them, For this, one field study and three laboratory experiments have been carried out. Among the most relevant results obtained it can be highlighted that: (I) both oysters and mussels are useful to properly indicate the health status of estuaries of the Bay of Biscay, yet higher accumulation of metals occurs in oysters than in mussels, (II) the intake pathway (watercolumn and/or food) induces different response intensities in oysters (III) the toxicity of Ag is enhanced in the presence of Cu in oysters and (IV) salinity has a low effect on the toxicity of both metals in oysters. Les estuaires ont été soumis à une forte pression humaine qui a entraîné la présence de polluants dans leurs eaux et sédiments, par exemple les métaux traces. Les estuaires du Golfe de Gascogne n’en sont pas une exception et les estuaires d’Ibaizabal et de la Gironde sont bien connus pour avoir des concentrations élevées de métaux. Dans ce contexte, les programmes de surveillance de l’environnement se sont appuyés sur l’utilisation des moules et des huîtres comme espèces sentinelles, car les analyses chimiques et biologiques de leurs tissus permettent d’évaluer l’état général ...